The Influence Of Brand Experience On Brand Loyalty Through Brand Satisfaction And Brand Trust In Indomie Mie In Sampit - Oetama, Seanewati; Susanto, Hari (International Journal of Science, Technology & Management, 2023)
The title of this study is about the effect of brand experience on brand loyalty through brand satisfaction and brand trust Mie Indomie in Sampit, East Kotawaringin Regency, Central Kalimantan Province. This research usespurposive sampling. And the data was tested using validity tests (convergent validity and discriminant validity), reliability tests, mediation tests andanalysisStructural Equation Model (SEM). Based on the results of the structural equation test, brand experience significantly influences brand satisfaction. With a part coefficient value of 0.700 and a p-value of 0.01, the hypothesis is accepted. In the structural equation test, brand experience significantly influences brand trust. With a part coefficient value of 0.749 and a p-value of 0.01, the hypothesis is accepted. In the structural equation test, brand experience significantly influences brand loyalty. With a part coefficient value of 0.745 and a p-value of 0.01, the hypothesis is accepted. In the structural equation test, brand satisfaction has no significant effect on brand loyalty. With a part coefficient value of 0.869 and a p-value of 0.01, the hypothesis is accepted. In the structural equation test, brand trust significantly influences brand loyalty. With a part coefficient value of 0.235 and a p-value of p=0.05, the hypothesis is accepted. In the structural equation test, brand experience has a significant effect on loyalty through brand satisfaction. The test results show thatmediation test for indirect effect with a significant value of P <0.01. While the direct effect with a significant value of 0.06. And the direct influence of the path coefficient value decreases from 0.75 to 0.16,so the hypothesis is accepted. In the structural equation test, brand experience has a significant effect on loyalty through brand trust. The test results show thatmediation test for indirect effect with a significant value of 0.31. While the direct effect with a significant value P <0.01. And the direct effect of the path coefficient value is decreasing from 0.75 to 0.36,so the hypothesis is accepted.